Doing Time Based on a Manga by Kazuichi Hanawa - Yoichi Sai; Hamada, Takeshi; Matsushige, Yutaka; Muramatsu, Toshifumi; Yamazaki, Tsutomu (Palour Pictures, 2006)
Prison films aren't usually described as lyrical or poignant, but then again there's never been a film quite like Sai Yoichi's "Doing Time". Based on the experiences of comic manga artist Hanawa Kazuichi, the film examines the absurdly regimented lives of five not-so-hardened criminals. The cons spend their days obsessing over menial chores, dutifully obeying the bizarre prison rules (where even doing a crossword puzzle can put you in solitary) and dreaming of their next delicious meal. Masterfully directed by Sai Yoichi (Blood and Bones) and featuring a stellar performance by Yamazaki Tsutsomu, "Doing Time" reveals that happiness can come in the most unlikely of places. [Cover]